Dialogue and hope in the classroom: a poetic inquiry into Freire's theories and their relationship to student activism - Robertson, Nyk (Kansas State University, 2023)
Current studies focus on critical pedagogy in the classroom as a practice, but do not connect these practices to praxis outside of the classroom as it relates to identity-based student activism. The purpose of this research is to investigate students’ experiences and development as identity-based student activists and the role of dialogue in the classroom on the development of civic identities at a Midwestern regional state institution through a lens of humanity as defined by Freire. This study aims to answer the following research questions: 1. How do college students construct civic identities? 2. How do college students participate in civic engagement? 3. In what ways do identity-based student activists engage with Freire’s concepts of dialogue and humanity? Participants of the study consisted of seven students from a Midwestern regional 4-year state institution. The seven students ranged from 18-24 years of age. Participants were identified through a recruitment process. First, students were enrolled in at least one class with a curriculum that utilizes social justice pedagogy as illustrated through the syllabus, course description, and learning activities employed. Data was collected through two semi-structured interviews with each participant individually and two focus groups conducted with 3-4 participants each group. Results are organized by five major clusters utilizing poetic inquiry. These clusters include critical pedagogy in the classroom, conflict, individual actions, collective influence, and barriers. These clusters offer suggestions that can be used in classrooms and across institutions as they focus on dialogue and civic engagement. These results can inform educators’ strategies based on successful activities and structures professors have utilized within the classroom, provide possibility models for curriculum and classroom design, and present suggestions on how institutions can more intentionally create space for critical deliberate dialogue.
Keywords: Dialogue; Poetic inquiry; Freire; Student activism